ANALISIS ONLINE CONSUMER REVIEWS DAN GREEN PRODUCT TERHADAP PURCHASE DECISION MELALUI TRUST SEBAGAI VARIABEL INTERVENING - Putri, Yessi Anggraeni; Lukitaningsih, Ambar; Fadhilah, Muinah (STKIP Persada Khatulistiwa Sintang, 2023)
In this study, trust will be used as a mediator to examine the elements that affect consumers' decisions to buy skin care goods at Sociolla. Quantitative research methodology is employed. 100 Sociolla consumers who bought Sukin goods in Indonesia are included in this study. Questionnaire-based data collection where answers are rated on a likert scale. Descriptive statistical analysis and inferential statistical analysis (SEM) based on variance, including the Measurement Model Indicator Test and Fit Model Test, are included in the data analysis process. testing of hypotheses using internal model testing findings. Based on the results of the analysis can be concluded that online customer reviews have a positive impact on consumer trust Sociolla, Green product has a positive effect on the trust of consumers Sociolla. Trust has no positive influence on purchase decisions, Online customer reviews have no positive impact on purchasing decisions. Green products have a positive impact on purchasing decisions. Trust variables do not play a role in measuring the influence of online customer reviews on consumer purchase decisions at Sociolla. Trust variables do not play a role in influencing the influence of green products on purchasing decisions at Sociolla.